Historiography and Social Memory: A History Construction in the Example of “Târîh-i Sefer-i Beç” Dated 1731 - Metin Aydar (Türkiyat Mecmuası)
Ottoman historiography boasts an extensive body of work, particularly on political and military developments. Among these, the 1683 Vienna Campaign holds a pivotal place as a turning point in Ottoman history, marking the end of the empire’s expansion dreams in Europe. This siege is equally significant in European history, influencing military and political landscapes. While contemporary sources detail the campaign’s process and outcomes, later historical texts offerunique interpretations of the event. One such text is the manuscript Târîh-i Sefer-i Beç (History of the Vienna Campaign), preserved in the National Library of France, Supplément Turc 870. This manuscript provides a comprehensive account of the campaign, presenting rare and original insights. This study examines Târîh-i Sefer-i Beç in comparison with other contemporary sources, evaluating its descriptions, language, and unique details, as well as its significance within the historiographical tradition. Written nearly half a century after the campaign, the manuscript offers a fresh perspective, reassessing the event’s place in Ottoman historiography. Its straightforward language and detailed content distinguish it as an important, albeit underappreciated, source. However, its singular copy and limited audience restricted its influence on social memory. Despite this, the work remains invaluable for understanding the broader implications of the Vienna Campaign and its historiographical impact, especially when compared to accounts by contemporaneous witnesses.